Desain Pemodelan Konsep Wide Area Protection (Wap) Di Sistem Transmisi Tenaga Listrik - Khumaini, M Rois; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study will be suggested to gather information in very wide area for appropriate decision making to overcome a fault. Some important things are implementing the Wide Area Protection (WAP) system using Measurement Phasor Unit (PMU) and Artificial Neural Networks (ANN) on the IEEE 14 bus electric power system. This 14 bus system is modeled using Matlab/Simulink. Then, the fault detection location runs on the electric power transmission line with a wide area of the system that has been modeled. The purpose of this study is to design WAP system on the IEEE 14 bus system based on the PMU and ANN. PMU functions to convert voltage and current waves into phasor forms, magnitude and angle of voltage and current function to identify the location of three-phase short circuit faults. PMU via Matlab/Simulink works well and, it can read the magnitude value and the angle of current and voltage on the entire bus. The simulation is performed on variations on ANN input data current and voltage. The results of the training and testing of ANN gave an accurate value of the input current of 89%, a voltage of 85% and a combination of current and voltage of 78%.Keywords: ANN, fault location, PMU, short circuit, WAP